SPIRITUAL ISLAM SUNDA DALAM TRADISI HAJAT SOLOKAN - Imam Setyobudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2011)
This article is the ethnographic notes on leutik Hajat Solokan, aritual ceremony of farmers in Babakan Dago, Rancakalong district,Sumedang West Jawa. This ceremony reflects wisdom values, such asprotecting and maintaining ecological systems which supports their mainjobs, cultivating rice fields. This article provides empirical evidence aboutculture system which packing religious values in order to make it sturdyand stay longer. The writer also found acculturation among some religiousvalues, Hinduism, Chinese, and Islam.